2020
DOI: 10.3346/jkms.2020.35.e288
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of COVID-19 Outbreak at Fitness Centers in Cheonan, Korea

Abstract: Background: In February 2020, a coronavirus disease 2019 (COVID-19) outbreak was reported in fitness centers in Cheonan, Korea. Methods: From February 24 to March 13, an epidemiological investigation was conducted on the fitness center outbreak. All those who were screened were tested for severe acute respiratory syndrome coronavirus-2 (SARS CoV-2) using real-time reverse transcriptase polymerase chain reaction. Contacts were traced and self-isolated for 14 days. We determined the epidemiological characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 15 publications
3
52
0
Order By: Relevance
“…We identified 54 relevant published studies that reported household secondary transmission, with 77 758 participants (eTable 1 in the Supplement ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 A total of 16 of 54 studies (29.6%) were at high risk of bias, 27 (50.0%) were moderate, and 11 (20.4%) were low (eTable 2 in the Supplement ). Lower quality was attributed to studies with 1 or fewer test per contact (35 studies [64.8%]), small sample sizes (31 [57.4%]), a...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 54 relevant published studies that reported household secondary transmission, with 77 758 participants (eTable 1 in the Supplement ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 A total of 16 of 54 studies (29.6%) were at high risk of bias, 27 (50.0%) were moderate, and 11 (20.4%) were low (eTable 2 in the Supplement ). Lower quality was attributed to studies with 1 or fewer test per contact (35 studies [64.8%]), small sample sizes (31 [57.4%]), a...…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 summarizes secondary attack rates for 44 studies 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 61 , 62 , 63 , 65 , 66 , 67 , 69 , 70 of household contacts and 10 of family contacts. 26 , 31 , 37 , 45 , 58 , 60 , 65 , 68 , 71 , 72 Estimated mean secondary attack rate for household contacts was 16.4% (95% CI, 13.4%-19.6%) and family contacts was 17.4% (95% CI, 12.7%-22.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the well-known negative health outcomes of chronic PM 2.5 exposure [ 1 , 4 , 5 ], several recent studies postulated that PM aerosols can also serve as a vector transporting bacteria and viruses through airborne diffusion, allowing them to penetrate deeply into the lungs and surpass the multilayer barriers of the respiratory system, thus enhancing SARS-CoV-2 virus transmission mechanism [ 13 , 14 ]. Such airborne transmission route for COVID-19 was suggested as a possible reason for mass indoor infections in restaurants, buses and fitness centers and in some cases via ventilation systems [ [26] , [27] , [28] ]. Such a route was also recognized by the CDC in 2020 under special circumstances such as: 1.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ]; who also concluded that “nearly all SSEs [super spreading events] in the database took place indoors.” [ 15 ] identified 318 outbreaks each with a minimum of 3 cases, comprising a total of 1245 confirmed cases in 120 prefectural cities in non-Hubei provinces, China, and found that none occurred in outdoor settings. High attack rates of COVID-19 have also been found in choir rehearsal [ 7 , 16 ], homeless shelters [ [17] , [18] , [19] ]; nightclubs [ 20 ]; Fitness centers [ 21 , 22 ] and meat processing plants [ 23 ]. Although airborne transmission has been suspected in many of these outbreaks, ventilation rates were not measured in the infection venues.…”
Section: Discussionmentioning
confidence: 99%